Information effect on voter turnout: how campaign spending mobilises voters - Trumm, Siim; Sudulich, Laura; Townsley, Joshua (Palgrave Macmillan, 2016)
We explore the impact of campaign effort on constituency-level turnout variation in Britain, under the premise that higher levels of campaign visibility stimulate electoral participation. We focus on the relationship between the competitiveness of the race and campaign effort as a provider of electoral information on the one hand, and voter turnout on the other hand. In doing so, we address the role of campaign effort and competitiveness in shaping turnout both independently as well as jointly. Further to this, we seek to add nuance to our understanding of how electoral campaigns mobilise voters by evaluating the comparative ability of different parties – based on whether or not they are ‘viable’ contenders in a particular constituency – to stimulate turnout. We find evidence that campaign effort mobilises voters and has a significant positive effect on voter turnout; this effect is independent from, and unconditioned by, the competitiveness of the race. However, we do find that this effect is mostly driven by the campaign effort of the ‘viable’ contenders in the constituency.